The Impact Of Ginger Aromatherapy On The Occurrence Of Nausea And Vomiting In Pregnant Women During The Initial Trimester At The Kersana Health Center In 2024 - Aprilia, Evi; Musfiroh, Sri; Tonasih, Tonasih; Ratnasari, Eka (Ann Publisher, 2024)
Ginger is an herbal medicinal ingredient that is efficacious in relieving coughs and sore throats, lowering bad cholesterol levels, relieving headaches, overcoming rheumatism, losing weight, maintaining heart health, overcoming nausea and digestive problems, preventing intestinal inflammation, improving the immune system, and cure asthma. Ginger acts as an aromatherapy treatment for nausea in pregnant women during the initial stage of pregnancy. The employed methodology is quasi-experimental, utilizing the one-group pretest and posttest design approach. This research design lacks a comparison group (control). However, the researcher conducts an initial observation (pretest) to assess the change. The study's independent variable is the use of ginger aromatherapy. The study focused on the dependent variables of nausea and vomiting experienced by pregnant women during the first trimester. The study findings demonstrated that ginger aromatherapy had a significant impact on reducing the occurrence of nausea and vomiting in pregnant women during the first trimester at the Kersana Brebes Health Center in 2024, shifting the severity from moderate to mild.